2006
DOI: 10.1002/eat.20282
|View full text |Cite
|
Sign up to set email alerts
|

Innovative interventions for disordered eating: Evaluating dissonance‐based and yoga interventions

Abstract: These findings have important implications for interventions on college campuses. In particular, dissonance interventions appear to be an efficient and inexpensive approach to reducing eating disorder risk factors. Additional research regarding the value of yoga interventions is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(99 citation statements)
references
References 38 publications
3
93
1
2
Order By: Relevance
“…CD has been studied by five independent labs (see for review of all studies; see also Green, Scott, Diyankova, Gasser, & Pederson, 2005;Matusek, Wendt, Wiseman, 2004;Mitchell, Mazzeo, Rausch, & Cooke;, and has been found to reduce the following ED risk factors: negative affect, internalization of the thin-ideal standard of female beauty, body dissatisfaction, maladaptive dietary restraint, and bulimic pathology . Two metaanalyses also found that ED prevention programs producing the largest effects were those that were interactive (not didactic), multi-session (not single session), and dissonance-based (not psychoeducational) (Stice & Shaw, 2004;Stice et al, 2007).…”
Section: Is One Of Very Few Ed Prevention Programs To Meet the Amementioning
confidence: 99%
“…CD has been studied by five independent labs (see for review of all studies; see also Green, Scott, Diyankova, Gasser, & Pederson, 2005;Matusek, Wendt, Wiseman, 2004;Mitchell, Mazzeo, Rausch, & Cooke;, and has been found to reduce the following ED risk factors: negative affect, internalization of the thin-ideal standard of female beauty, body dissatisfaction, maladaptive dietary restraint, and bulimic pathology . Two metaanalyses also found that ED prevention programs producing the largest effects were those that were interactive (not didactic), multi-session (not single session), and dissonance-based (not psychoeducational) (Stice & Shaw, 2004;Stice et al, 2007).…”
Section: Is One Of Very Few Ed Prevention Programs To Meet the Amementioning
confidence: 99%
“…They have also shown significant reduction of eating disorder and Binge Eating Disorder. 8,[10][11][12][13] (Table 2) Following courses of yoga and meditation reduction in outcomes under study viz. alcohol use, craving for alcohol and dependence on alcohol, was reported.…”
Section: Results:-mentioning
confidence: 99%
“…The criteria for exclusion were:  studies other than Randomized Controlled Trial  multiple interventions given simultaneously to study group 339  control groups receiving some other intervention Finally 15 articles were eligible to be included for review. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Data was extracted from the selected articles and sorted according to outcomes studied and arranged in tables in chronological sequence. Though inclusion criteria were kept as publications in past 50 years, only 2 studies published in the last millennium were eligible to be included.…”
Section: Materials and Methods:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Applications to health care and nursing are not plentiful. Most prominently, Totman (1976) applied dissonance theory to the placebo effect, and dissonance has also been linked with treatment of depression (Tryon & Misurell, 2008) and eating disorders (Mitchell et al, 2007). Specific to nursing, Taylor and Bentley (2005) coined the term professional dissonance to understand conflict between practice and care values in mental health nursing.…”
Section: Nurse Educationmentioning
confidence: 99%